Characterization of a novel HLA‐DRB1 allele: DRB1*11:153. Issue 4 (11th January 2014) - Santos, S.; Balas, A.; Azcarate, M.; Vesga, M. A.; Vicario, J. L.
<x xml:space="preserve">Abstract</x> HLA‐DRB1*11:153 differs from DRB1*11:131 by one nucleotide at position 286 where C > A, (codon 67 CTC>ATC), resulting in an amino acid substitution, 67L>67I.